Developing the Quality of Mathematics Education to Improve Students' Mathematical Ability - Mendrofa, Netti Kariani; Yusup, Muhammad; Rahmani, Anggi; Samputri, Salma; Sappaile, Baso Intang (Abdimas Indonesian Journal, 2024)
Learning represents a fundamental aspect of the educational process. The efficacy of the learning process is a key determinant of the extent to which educational objectives are achieved. Similarly, the quality of mathematical learning is a significant predictor of success in mathematics. The objective of this thesis is to examine the potential of managerial strategies to enhance the quality of mathematics learning. This research employs a qualitative methodology, specifically a case study design. Data were collected through in-depth interviews. The data sources, or resource persons, were selected using the snowball technique. The data were validated through the triangulation technique. The results demonstrated that: (1) The management of improvements to the quality of mathematics learning is conducted in three stages: planning, implementation, and assessment. (2) Teachers employ various strategies to enhance mathematics learning outcomes, including the provision of structured assignments. (3) The effective management of learning outcomes is contingent upon three key supporting factors: parental involvement, access to learning resources, and the principal's leadership model. (4) Persistent challenges, such as the pervasive belief that mathematics is inherently challenging and student motivation, must also be addressed.